Development of stem-based E-LKPD on substance pressure material to improve critical thinking skills of junior high school students - Kiswari, Lusida; Singgih, Suwito; Siswanto, Siswanto (IAIN Palangka Raya, 2023)
This research aims to analyze the feasibility, effectiveness, and practicality of STEM-based E-LKPD. The type of research used is the R&D model which is modified into 7 stages, namely needs analysis, product design, design validation, design revision, product trial, product revision, and usage trial. The research results showed that the feasibility of STEM-based E-LKPD was declared quite valid or suitable for use with a percentage of 72.5%. Effectiveness is measured based on students' pretest and posttest scores in usage trials with a sample of 28 students. The pretest and posttest values explained produce data that is normally distributed and homogeneous. The increase in pretest and posttest scores was tested using N-Gain with a calculation result of 0.64 in the medium category. The level of product effectiveness was tested using an effect size with a result of 3.4 with high criteria. The practicality test of STEM-based E-LKPD was obtained by teachers at 97.3% and students at 84.4% in the very practical category.